PENGELOLAAN BARANG MILIK DAERAH DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN ROKAN HULU TAHUN 2017 - Jumadi Afdhol; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Management of local assets, Rokan Hulu District since the year formed until the Year 2015 has developed a policy of regional assets in the form of management of regional property as a rule issued by the central government, and from 2007 to 2015 refer to the Minister of Home Affairs Regulation No. 17 of 2007 on Guidelines Technical Management of Regional Assets, and derivatives thereof issued by the Regent of Rokan Hulu Regulation No. 38 Year 2011 on Inventory Management System and Procedures and Administration. Observing field data found weaknesses in managing movable assets and fixed assets in the Secretariat of the House of Representatives of Rokan Hulu Regency Year 2017. The problem in this study is how the management of local property in the Secretariat of the Regional Representative Council of Rokan Hulu Regency Year 2017 and what factors - the factors that block it. The purpose of this study is to know the Management of Regional Property At the Secretariat of the House of Representatives of Rokan Hulu Regency Year 2017, and to know the factors that hinder it.In this research, the researcher uses descriptive research type with qualitative method approach. The research is located in the Secretariat of the House of Representatives of Rokan Hulu District. For informant research using purposive sampling technique. Data collection techniques used are observation, interview and documentation. To examine the problem the authors perform data analysis using qualitative descriptive method.The results of this study can be concluded that the management of local property in the Secretariat of the Regional Representative Council of Rokan Hulu Regency in 2017 has not gone well. The ineffectiveness of the management of regional assets with due regard to the consideration of the Secretariat of the Regional House of Representatives is less aware of the importance and supervision. To that end, the Secretariat of the Regional People's Legislative Assembly shall endeavor to realize the effective management of regional assets in Rokan Hulu Regency. Obstacles in the management of local property in the Secretariat of the Regional Representative Council of Rokan Hulu Regency Year 2017, namely: (1) Insufficient human resources, (2) Lack of understanding and attention, (3) Limited facilities and infrastructure, (4) Absence strict sanctions.Keywords: Management, Regional Property.